Aquaguard-on-the-Go: Purified Water Anywhere Anytime. (June 2017) - Vandana; Kumar, Vinod; Lenka, Usha
Shapoorji Pallonji Group's Eureka Forbes has reached 15 million customers in 550 cities of India and 35 countries globally (Sharma, 2014). Harvard Business Review has cited Eureka Forbes among six most successful sales and marketing companies in the world (Legal Era, 2012). This home appliances company has expanded its footprint by introducing a mobile water purifier Aquaguard-on-the-Go under the brand Aquaguard. Marzin R. Shroff, Eureka Forbes CEO, has claimed that Aquaguard-on-the-Go is 'an important milestone in the history of brand Aquaguard which will take their market leadership in India to the next level' ( Business Line, 2014). The company is excited about this product, but the question is how the company should reach target customers of this product in Indian market.